THE EFFECT OF THE USE OF ALCOHOL AND DRUGS ON MOTORCYCLICAL TRAUMAS WITH SURGICAL TREATMENT FRACTURES: EPIDEMIOLOGY - FERNANDO ARAUJO PIRES; JOÃO BAPTISTA GOMES DOS SANTOS; RENATO HIROSHI SALVIONI UETA; FLÁVIO FALOPPA; VINICIUS YNOE DE MORAES; MARCEL JUN SUGAWARA TAMAOKI (Acta Ortopédica Brasileira, 2022)
ABSTRACT Objective: To verify the prevalence of patients who were victims of motorcycle trauma who were under the influence of alcohol and drugs. Methods: The study was observational and prospective, with patients hospitalized to the Orthopedics and Traumatology Ward of Hospital São Paulo (UNIFESP), from March 2015 to March 2016. The study included patients of all genders, over 18 years old, hospitalized due to motorcycle trauma and who needed orthopedic surgical treatment. Results: During the research, 282 patients were hospitalized, of which 23.8% were victims of motorcycle trauma. Of these, 49.3% motorcyclists reported the use of alcohol and drugs before the accident, while 50.7% denied their consumption. In the analysis of alcohol and drug consumption in patients with motorcycle injuries, the results showed that: 65% used only alcohol; 16% used both alcohol and drugs; and 19% used only illicit drugs. Conclusion: The incidence of patients who suffered motorcycle accidents under the influence of alcohol and drugs was 49.3%. Level of Evidence IV, Prospective Case Series.